Teori Keadilan Kontemporer (Sebuah Kajian Teori Hukum) - La Ode Muhammad Iman Abdi Anantomo Uke (Al-'Adl, 2017)
Studying the science of law can not be separated by the existence of legal theory. The term theory comes from the English language theory, and in Dutch theorie. Theory also comes from the word "theoria" which in Latin means "contemplation" and in the Greek "thea" which essentially implies something called reality. Some scholars use the word theory to show structured, logical (rational), empirical (reality) thinking, as well as symbolic. While the law itself from the English term law, and the Dutch language is recht. John Austin defines the law as a rule that is held to provide guidance to the intelligent beings by the intelligent beings who rule over it. The theory of law itself comes from the English language that is theory of law and in Dutch called rechtstheorie which means the branch of Law Science which in an interdisciplinary perspective critically analyzes various aspects of legal phenomena each in isolation and in overall relation both in theoretical conception As well as in practical translation by referring to a better understanding and a clear explanation of juridical material. Critically analyzing a legal theory in the presence of thesis and anti-thesis in an ever-expanding theoretical study as a study material in the academic world of law. For that reason John Rawls's contemporary justice theory known as "A Theory of Justice" becomes interestingly studied and criticized as a study.